2019
DOI: 10.1590/0102-311x00230418
|View full text |Cite
|
Sign up to set email alerts
|

Violência urbana e fatores de risco relacionados ao feminicídio em contexto amazônico brasileiro

Abstract: Resumo: Apesar de sua gravidade, o feminicídio é pouco investigado e suas estimativas dependem das estratégias usadas à sua caracterização, do contexto sociocultural e político. Este estudo teve como objetivo avaliar os homicídios intencionais de mulheres, com enfoque nos feminicídios, destacando suas características e fatores de risco. Estudo transversal, baseado em vigilância diária de homicídios na imprensa e em registros de mortalidade. Foram consideradas vítimas fatais por agressões, mortes de mulheres ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
(56 reference statements)
0
5
1
2
Order By: Relevance
“…In different places, however, the means employed by the aggressor varies, with a higher prevalence of the use of sharp objects, as observed in Manaus, capital of the state of Amazonas, and in the municipality of Campinas, state of São Paulo. 21 , 24 In this type of homicide, besides the victim being killed, they are also often disfigured, with a high number of wounds on the face, indicating hate crimes or crimes motivated by banal and futile reasons. 10 , 23…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In different places, however, the means employed by the aggressor varies, with a higher prevalence of the use of sharp objects, as observed in Manaus, capital of the state of Amazonas, and in the municipality of Campinas, state of São Paulo. 21 , 24 In this type of homicide, besides the victim being killed, they are also often disfigured, with a high number of wounds on the face, indicating hate crimes or crimes motivated by banal and futile reasons. 10 , 23…”
Section: Discussionmentioning
confidence: 99%
“… 11 Factors such as unemployment, drug trafficking, family breakdown, and social inequality, especially among youth, exacerbate structural violence and increase women’s vulnerability, with greater impact on gender-based violence. 24 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…The results showed that literacy was characterized as a risk factor for violence in older adult women, diverging from the literature, which states that older adults with low schooling levels are more likely to suffer abuse (27) . However, another study asserted that the risk of sexual or physical violence increases as the years of study increase (28) . The prevalence of risk among the older adults can be justified by the better perception of violence among those with a higher schooling level.…”
Section: Discussionmentioning
confidence: 99%
“…No Brasil, essas violências constituem um problema de extrema importância, tendo em vista que, mundialmente, o país ocupa o 5º maior risco de óbitos por homicídios femininos (Nowak, 2012). Quando analisadas as principais regiões do corpo atingidas durante as agressões, observa-se que as vítimas sofrem mais lesões na região de cabeça e pescoço (Orellana et al, 2019).…”
Section: Introductionunclassified